New records of polypores (Basidiomycota) from the state of São Paulo, Brazil - Pires, Ricardo Matheus; Motato-Vásquez, Viviana; Gugliotta, Adriana de Mello (Iheringia, Série Botânica., 2016)
The diversity of polypores in Brazil is still poorly known. During a survey of this group in Parque Estadual da Serra do Mar, Núcleo Santa Virgínia, São Paulo state, undertaken from April 2013 to April 2014, the species Cinereomyces dilutabilis (Loguercio-Leite & J.E. Wright) Miettinen, Flaviporus brownii (Humb.) Donk, F. subhydrophilus (Speg.) Rajchenb. & J.E. Wright, Fomitiporia bambusarum (Rick) Campos-Santana & Decock, Inonotus tropicalis (M.J. Larsen & Lombard) T. Wagner & M. Fisch., Junghuhnia carneola (Bres.) Rajchenb., Rigidoporus crocatus (Pat.) Ryvarden and Skeletocutis nivea (Jungh.) Jean Keller were found as new records for the state of São Paulo and Dichomitus cylindrosporus Ryvarden as a new record for Brazil. Full descriptions, illustrations and remarks on the species are provided.